2013
DOI: 10.1007/s00114-013-1076-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exotic fish farms on bird communities in lake and marine ecosystems

Abstract: Salmon farming is a widespread activity around the world, also known to promote diverse environmental effects on aquatic ecosystems. However, information regarding the impact of salmon farming on bird assemblages is notably scarce. We hypothesize that salmon farming, by providing food subsidies and physical structures to birds, will change their local community structure. To test this hypothesis, we conducted a seasonal monitoring of bird richness, abundance, and composition at paired salmon pen and control pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The birds perched on farm structures to rest, roost, and preen. In Chile, Jiménez et al 274 observed higher seabird abundance at salmon pens compared with their control sites and found salmon farming had no significant effect on avian species richness. The primary species included diving piscivores, perching piscivores, omnivores, and carrion eaters but did not include herbivores, invertebrate, or surface feeders.…”
Section: Protected Species and Marine Aquaculturementioning
confidence: 97%
“…The birds perched on farm structures to rest, roost, and preen. In Chile, Jiménez et al 274 observed higher seabird abundance at salmon pens compared with their control sites and found salmon farming had no significant effect on avian species richness. The primary species included diving piscivores, perching piscivores, omnivores, and carrion eaters but did not include herbivores, invertebrate, or surface feeders.…”
Section: Protected Species and Marine Aquaculturementioning
confidence: 97%